THE ROLE OF JUSTICE COLLABORATOR IN UNCOVERING CRIMINAL CASES IN INDONESIA - Hambali Thalib; Sufirman Rahman; Abdul Haris Semendawai (Diponegoro Law Review, 2017)
The purpose of this research is to study the role of justice collaborator in uncovering who is the mastermind behind a major crime in the act of criminal law, and also not only end on a minor defendant (field defendant). The empirical law research methods is conducted on the Commission Eradication Commission (KPK) and the Witness and Victim Protection Agency (LPSK). The results shows that the role of justice collaborator facilitates the verification in the criminal judicial process in order to totally reveal the well-organized transnational crime. In this context, corruption in Indonesia is committed collectively, the existence of regulations on justice collaborator is a legal instrument that is expected to strengthen the collection of Form of Evidence dan Real Evidence at the trial